Singaporeans' general investment needs towards retirement planning. - Chung, Bao Yin. (2009)
To ensure sufficient funds for retirement, one will have to look for alternative income resources. Our survey helps to collect data on Singaporeans’ general investment preferences towards retirement planning and their investment return expectations relative to their risk acceptance level. From the results of our survey, we will explore the various factors affecting people’s investment decisions and recommend appropriate financial products for their retirement portfolios.